Drag on a Circular Cylinder Oscillating in a Dusty Viscous Fluid - Indrasena, A.; Awin, Ali Mohamed (Engineering Transactions, 1983)
Rectilinear oscillations of а circular cylinder in an infinite expanse of а viscous, imcompressible fluid with embended small solid spherical particles are studied. Analytical expressions for the velocity of the fluid and the drag experienced bу the cylinder due to fluid stress are given. Explicit expressions for the drag parameters are obtained using the asymptotic expansion of modified Bessel functions, and some limiting cases are discussed.